2023
DOI: 10.1002/adfm.202301377
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Efficiency Improvement for CZTSSe Solar Cells with over 12% Efficiency via Ga Incorporation

Abstract: Suppressing the band tailing and nonradiative recombination caused by massive defects and defect clusters is crucial for mitigating open-circuit voltage (V oc ) deficit and improving the device performance of CZTSSe thin film solar cells. Cation substitution is one of the most commonly used strategies to address the above issues. The latest world record efficiency of 13.0% is obtained through this strategy (Ag substitution for Cu). Nevertheless, the importance of the approach to implementing metallic ion dopin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…On the other hand, chemical doping of the Ga element not only improved the crystallinity of the absorber layer but also increased the depletion width of the device, reduced the concentration of deep-level defects and Urbach energy, and improved the device efficiency to 12.12%. 109…”
Section: Present Status Of Solution-processing Routes For High-effici...mentioning
confidence: 99%
“…On the other hand, chemical doping of the Ga element not only improved the crystallinity of the absorber layer but also increased the depletion width of the device, reduced the concentration of deep-level defects and Urbach energy, and improved the device efficiency to 12.12%. 109…”
Section: Present Status Of Solution-processing Routes For High-effici...mentioning
confidence: 99%
“…In 2018, Yao et al 36 reported that lndoping can lead to the formation of the ln Sn acceptor, which subsequently enhances hole concentration and device performance. Recently, Liu et al 21 have also demonstrated that the incorporation of Ga can effectively suppress nonradiative recombination and deep defect states in CZTSSe, thereby enabling a significant improvement in both V OC and shortcircuit current density (J SC ) in tandem, resulting in an efficiency boost from 10.49 to 12.12%. The aforementioned successful cases demonstrate the feasibility of incorporating III-A elements into CZTSSe to enhance the device performance.…”
Section: Introductionmentioning
confidence: 99%
“…The main limitations to the enhancement of PCE in CZTSSe solar cells are acknowledged to be the low open-circuit voltage ( V OC ) and fill factor ( FF ), primarily attributed to bulk cation disorder and associated band tailing within the absorber, unpassivated interfacial defects, as well as unfavorable band alignment at both the heterojunction interface (HEI) and back electrode interface (BEI). , In order to achieve a superior absorber and interface, as well as high efficiency, numerous optimization strategies have been employed to address these issues, including cation doping, passivation of interfacial defects and bulk grain boundaries, ,, field passivation effect construction, gradient band gap design, etc. Among them, the cation doping method is widely utilized to reduce bulk disorder and band tailing for the achievement of high V OC (and FF ).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Furthermore, doping with +3-valent cations reduces the Zn-and Sn-related defects, whereas doping with +4-valent cations reduces the Sn-related deep-level defects. [8][9][10][11][12][13][14] These methods have indeed improved the efficiency, but the highest efficiency of the CZTSSe device at present is still less than 15% for commercial applications. Thus, further optimization of the device fabrication process, especially for the grain growth of the CZTSSe absorber layer, may facilitate an improvement in efficiency.…”
Section: Introductionmentioning
confidence: 99%